Hungarian Monitoring, 18 December 1989 . [Magyar rádiófigyelő], 1989. december 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Events in Transylvanian towns - Slovak CP has new leadership - GDR-FRG: demonstrations in Leipzig, Kohl on German re-unification - Panama-America incident - V. Havel's presidential candidacy Domestic Affairs: - Government in session - Kohl's speech in the parliament, press conference - More than 40,000 people take part in candlelit demonstration called by Hungarian Democratic Forum (MDF) at Heroes' Square to defend Transylvania and László Tőkés - Hungarian Socialist Party (MSZP) party meeting - Hungarian Socialist Workers' Party (MSZMP) congress, leadership elections - Zionist youth museum to be re-opened Economy: - Draft law on state property and property protection - Mátyás Szűrös statement on the IMF's strict conditions - EEC approves USD 1 billion bridging loan Külpolitika: - Az erdélyi városokban lezajlott események - Új vezetősége van a szlovák kommunista pártnak - NDK - NSZK: lipcsei tüntetés, Kohl a német újraegyesítésről - A panamai-amerikai incidens - V. Havel elnökjelöltsége Belpolitika - Kormányülés - Kohl beszéde a Parlamentben, sajtótájékoztató - Az MDF felhívására ma több mint 40 ezer ember fáklyás demonstrációt tartott a Hősök terén, Erdély és Tőkés László védelmére - MSZP pártértekezlet - MSZMP kongresszus, vezetőségválasztás - A cionista ifjúsági múzeum újraindítása Gazdaság: - Az állami vagyonról, vagyonvédelemről szóló javaslat - Az IMF szigorú feltételeiről nyilatkozik Szűrös Mátyás - Az EGK jóváhagyta az 1 milliárd dolláros áthidaló kölcsönt